Justice, legitimacy, and movement across borders - Yong, C (2014)
Existing moral reflection on immigration law and policy is caught in an impasse between (1) proponents of an individual right to free international migration and (2) proponents of a state’s right to control its borders. In Chapter 1, I examine arguments supporting an individual right to free international migration. I show that the case for this putative right cannot be settled solely by considering the strength of individuals’ interest in being able to cross international borders according to their choice. Rather, at a crucial point, the argument for an individual right to free migration turns on the truth of a particular conception of global justice. In Chapter 2, I examine arguments supporting a state’s right to control its borders. I contend that these arguments do not seek to defend the substantive justice of restrictive immigration policies, but rather the legitimacy of processes of political decision-making by which states unilaterally determine their own immigration policies. Abandoning this right-versus-right paradigm, I recast the debate by focusing on two distinct questions: (1) the question of justice in immigration, which substantively evaluates immigrant admission policy; and (2) the question of the legitimacy of immigration law enacted by procedures responsive only to states’ internal political decisions. I further propose that in articulating principles of justice in immigration, we should first develop a conception of global justice which will provide the background for our evaluation of immigration policy. In Chapter 3, I develop and defend a conception of global justice I call cooperation-based internationalism. I argue that co-citizens are joint participants in a scheme of cooperation which provides them with the social goods they need to lead autonomous lives. They therefore owe each other special duties of social justice. In addition, I argue for a duty of assistance which applies among all human persons globally. This duty requires developed states to assist developing states in establishing minimally just institutions. In Chapter 4, I develop a conception of justice in immigration against the background of cooperation-based internationalism. I argue that there is no requirement for states to allow open immigration. Nevertheless, I argue that co-citizens owe each other duties which impose significant moral constraints on immigration policy: states must (1) allow for family unification; (2) eschew policies that select immigrants based on criteria that unjustly call into question the fitness for citizenship of certain current members; (3) regulate labour immigration so that all current citizens benefit equally unless unequal gains benefit worse-off citizens. The duty of assistance is also imposes constraints on immigration policy. Developed states should (4) avoid immigration policies which cause brain drain harmful to international development and (5) admit and resettle refugees. In Chapter 5, I turn to the distinct question of the legitimacy of unilaterally-enacted immigration law. I argue that the application and enforcement of immigration law counts as a coercive exercise of political power which stands in need of justification. I examine the consent and natural duty of justice theories of political legitimacy, concluding that these influential theories cannot establish the legitimacy of immigration law. I conclude by considering the implications of the illegitimacy of immigration law for the evaluation of irregular migration.